Solar Wind Plasma Properties During Ortho-Parker IMF Conditions and Associated Magnetosheath Mirror Instability Response - Génot, V.; Lavraud, B. (Frontiers in Astronomy and Space Sciences, 2021)
The properties of the solar wind fraction that exhibits an Interplanetary Magnetic Field (IMF) orientation orthogonal to the classical Parker spiral (so-called ortho-Parker) are investigated. We make use of the plasma categorization scheme proposed by \cite{Xu_Borovsky_2015} using 10 years of OMNI data and show that the fractions of the different plasma origins (streamer-belt-origin plasma, coronal-hole-origin plasma, sector-reversal-region plasma and ejecta) used in this scheme are rather constant when expressed as a function of the IMF orientation whereas the Alfv\'en Mach number significantly depends on this orientation. This has direct implication on the magnetosheath dynamics and, as an example, the stability of the mirror mode in this compressed plasma is studied thanks to Rankine-Hugoniot anisotropic relations. This study sheds light on previously reported, yet unexplained, observations of a larger occurrence of mirror mode in the magnetosheath downstream of ortho-Parker IMF.